Masticatory muscles activities in temporomandibular joint internal derangement. - Lafrenière, Chantal M. (University of Ottawa (Canada), 1995)
Intramuscular EMG of the lateral pterygoid muscles, surface EMG of the temporalis and masseter muscles, electrogoniometry and force measurements of the TMJ were synchronously used to investigate the biomechanical role of the two portions of the lateral pterygoid muscle in relation to internal derangement (ID) of the temporomandibular joint (TMJ). This study dealt with the EMG analysis of five static conditions: resting, resisted protraction, maximum voluntary contraction (MVC) in opening, in molar and incisor clenching of TMJ ID and control subjects. The analysis of variance results of the integrated linear envelop (LE) EMG showed no significant differences between the two groups. The integrated LE EMG of the SLP was significantly lower in the TMJ group during molar clenching (104$\mu$V $\pm$ 60.0 over 159$\mu$V $\pm$ 68.8 for a p =.020). The SLP seemed to have lost its discal stabilizing function during clenching. The integrated LE EMG signals of the ILP were significantly higher in the TMJ ID group during rest, resisted protraction and incisor clenching (p =.029, p =.046, p =.031 respectively). The ILP muscle has probably adapted to control the inner joint instability while continuing its own actions. The results of the isometric forces showed that TMJ ID subjects exhibited significantly lower molar bite forces (297.1N over 419N, p =.042) confirming that they have less muscle strength and tissue tolerance than subjects with healthy masticatory muscle system. Incisor bite forces, however, showed a tendency to be higher in the TMJ ID group (233N over 180.5N, p =.168), possibly resulting from the training of a protracted bite and/or hyperactivity of the ILP associated with ID. Therefore a neuromuscular adaptation could be occurring in TMJ ID masticatory system affecting muscular actions and forces. (Abstract shortened by UMI.)
Keywords: Biology, Anatomy.